An Operational Architecture for Improving Air Force Command and Control Through Enhanced Agile Combat Support Planning, Execution, Monitoring, and Control Processes - Lynch, Kristin F. (RAND Corporation, 2014)
Currently, agile combat support (ACS) planning, execution, monitoring, and control processes are poorly integrated with operational planning processes and have little ability to show how resource allocation decisions would impact planned and potential operations. This report presents a refined architecture based on previous RAND-developed operational architectures that depicts how, in the next 4-5 years, enhanced ACS processes could be integrated into Air Force command and control to provide senior leaders with enterprise ACS capability and constraint information.